Utilization patterns and efficiency gains from use of a fully EHR-integrated COVID-19 self-triage and self-scheduling tool: a retrospective analysis. (27th August 2022) - Judson, Timothy J; Pierce, Logan; Tutman, Avi; Mourad, Michelle; Neinstein, Aaron B; Shuler, Gina; Gonzales, Ralph; Odisho, Anobel Y
Abstract: Objective: Symptom checkers can help address high demand for SARS-CoV2 (COVID-19) testing and care by providing patients with self-service access to triage recommendations. However, health systems may be hesitant to invest in these tools, as their associated efficiency gains have not been studied. We aimed to quantify the operational efficiency gains associated with use of an online COVID-19 symptom checker as an alternative to a telephone hotline. Methods: In our health system, ambulatory patients can either use an online symptom checker or a telephone hotline to be triaged and connected to COVID-19 care. We performed a retrospective analysis of adults who used either method between October 20, 2021 and January 10, 2022, using call logs, electronic health record data, and local wages to calculate labor costs. Results: Of the 15 549 total COVID-19 triage encounters, 1820 (11.7%) used only the telephone hotline and 13 729 (88.3%) used the symptom checker. Only 271 (2%) of the patients who used the symptom checker also called the hotline. Hotline encounters required more clinician time compared to those involving the symptom checker (17.8 vs 0.4 min/encounter), resulting in higher average labor costs (24.21 vs 0.55 per encounter). The symptom checker resulted in over 4200 clinician labor hours saved. Conclusion: When given the option, most patients completed COVID-19 triage and visit scheduling online, resulting in substantial efficiency gains. These benefits may encourage health system investment in such tools.